HIV-1 diagnostic, prognostic and ART-resistance detection potential of selected MiRNAs - Karen Pomeyie; Joseph Humphrey Kofi Bonney; Benjamin Amoani; Roland Osei Saahene; Nicholas Ekow Thomford; Wishwell Pomeyie; Francis Abrokwah; Helena Quayson; Salisu Kalaamullah Musah; Selina Appiah; Deborah Pratt; Magdalene Sarah Ofori; et al. (BMC Infectious Diseases)
Abstract Background The global HIV prevalence estimate at the end of 2022 was 39 million. This has led to mass testing to diagnose new cases, and the conduction of prognostic tests for monitoring HIV progression. This is being done to meet the targets of the 95%: 95%: 95% UN AIDS goal which is to be achieved by 2025. Therefore, there is the need to discover other diagnostic and prognostic biomarkers to be supplemented with the currently used ones. Studies indicate that micro RNAs have their levels influenced by the presence and replication of aetiologic agents, thus the micro RNA (miRNA) expression profile test may serve the dual purpose of HIV diagnosis and prognosis. Therefore, this study assessed the HIV-1 diagnostic and prognostic potential of the expression patterns of circulating miRNAs in HIV positive persons in Cape Coast, Ghana. Methods A cross-sectional research design was used to assess the expression patterns of seven miRNAs – hsa-mir-146a, hsa-mir-155, hsa-mir-34a, hsa-mir-29a, hsa-mir-29b, hsa-mir-223 and hsa-mir-27a in 72 plasma samples. The samples were obtained from six antiretroviral therapy naïve persons, 37 ART-experienced persons and 29 healthy controls. Total RNA was extracted, afterwards, cDNA synthesis and RT-qPCR was done. Results There were low levels of hsa-mir-155, and elevated levels of two miRNAs – hsa-mir-34a, and hsa-mir-27a in ART-experienced persons relative to healthy control. The sensitivities of the above miRNAs were 82.14%, 72.73% and 81.25 respectively, and specificities were 86.21%, 70.59% and 87.50% respectively. Upregulated levels of hsa-mir-223 was associated with HIV-1 infection in ART-naïve persons. Hsa-mir-223, hsa-mir-155, hsa-mir-29a and hsa-mir29b were present in quantities that distinguished between viral load categories classified as very low and high. These miRNAs were correlated with viral load. Low levels of hsa-mir-155 in HIV-1 persons with viral load of less than 7cps/ml distinguished them from HIV-negative control. Increased levels of hsa-mir-146a correlated with ART-resistance. Conclusion Decreased levels of hsa-mir-155, and elevated levels of hsa-mir-34a, hsa-mir-223 and hsa-mir-27a could be biomarkers of HIV-1. Hsa-mir-155, hsa-mir-29a, hsa-mir29b and hsa-mir-223 could be good biomarkers of HIV-1 progression and Low levels of hsa-mir-155 may possess the potential to detect minute HIV-1 RNA copies. Elevated levels of hsa-mir-146a could be a potential biomarker of ART-resistance.